Optimizing students’ motivation through PBL-based worksheets in teaching circles: A classroom action research in Grade 7 - Agung Rivansyah; Agung Deddiliawan Ismail; Ayu Kurniawati (Universitas Muhammadiyah Malang, 2024)
This study employed a classroom action research (CAR) design, conducted in two cycles, each comprising four stages: planning, action, observation, and reflection. The research was carried out in Grade 7 at SMPN 03 Batu. Data were collected through questionnaires, observations, interviews, and documentation. The findings indicate a significant increase in students’ motivation to learn mathematics following the implementation of Problem-Based Learning (PBL)-based student worksheets (LKPD). The percentage of students’ learning motivation exceeded the success indicator, reaching 72%, which falls under the